Amorphous/Crystalline Hetero‐Phase Pd Nanosheets: One‐Pot Synthesis and Highly Selective Hydrogenation Reaction. Issue 39 (14th August 2018) - Yang, Nailiang; Cheng, Hongfei; Liu, Xiaozhi; Yun, Qinbai; Chen, Ye; Li, Bing; Chen, Bo; Zhang, Zhicheng; Chen, Xiaoping; Lu, Qipeng; Huang, Jingtao; Huang, Ying; et al.
Abstract: Similar to heterostructures composed of different materials, possessing unique properties due to the synergistic effect between different components, the crystal‐phase heterostructures, one variety of hetero‐phase structures, composed of different crystal phases in monometallic nanomaterials are herein developed, in order to explore crystal‐phase‐based applications. As novel hetero‐phase structures, amorphous/crystalline heterostructures are highly desired, since they often exhibit unique properties, and hold promise in various applications, but these structures have rarely been studied in noble metals. Herein, via a one‐pot wet‐chemical method, a series of amorphous/crystalline hetero‐phase Pd nanosheets is synthesized with different crystallinities for the catalytic 4‐nitrostyrene hydrogenation. The chemoselectivity and activity can be fine‐tuned by controlling the crystallinity of the as‐synthesized Pd nanosheets. This work might pave the way to preparing various hetero‐phase nanostructures for promising applications. Abstract : Amorphous/crystalline heterophase Pd nanosheets exhibit crystallinity‐dependent chemoselectivity and catalytic activity.